The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1063/1.4765717
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering study of bulk and nanocrystalline PbMoO4 at high pressures

Abstract: Effect of Li+ ions on enhancement of near-infrared upconversion emission in Y2O3:Tm3+/Yb3+ nanocrystals J. Appl. Phys. 112, 094701 (2012) Long range coupling between defect centres in inorganic nanostructures: Valence alternation pairs in nanoscale silica J. Chem. Phys. 137, 154313 (2012) Pressure dependence of the Verwey transition in magnetite: An infrared spectroscopic point of view J. Appl. Phys. 112, 073524 (2012) Silver nanoisland enhanced Raman interaction in graphene Appl. Phys. Lett. 101, 153… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…5E g . From these, we observe 11 modes in the Raman spectrum of PbMoO 4 single crystal due to accidental degeneracy of the A g and the B g modes at 318 cm -1 and the lower than the measured region frequency of the E g mode (*60 cm -1 ) [66]. The frequencies of the observed Raman peaks are in excellent agreement to those earlier reported in the literature [27,[65][66][67].…”
Section: Xrd Raman and Sem/eds Studiessupporting
confidence: 86%
See 1 more Smart Citation
“…5E g . From these, we observe 11 modes in the Raman spectrum of PbMoO 4 single crystal due to accidental degeneracy of the A g and the B g modes at 318 cm -1 and the lower than the measured region frequency of the E g mode (*60 cm -1 ) [66]. The frequencies of the observed Raman peaks are in excellent agreement to those earlier reported in the literature [27,[65][66][67].…”
Section: Xrd Raman and Sem/eds Studiessupporting
confidence: 86%
“…From these, we observe 11 modes in the Raman spectrum of PbMoO 4 single crystal due to accidental degeneracy of the A g and the B g modes at 318 cm -1 and the lower than the measured region frequency of the E g mode (*60 cm -1 ) [66]. The frequencies of the observed Raman peaks are in excellent agreement to those earlier reported in the literature [27,[65][66][67]. Similarly to the XRD measurements, Pb-sorption onto the AHM-derived MoO 3 causes the appearance of additional Raman peaks to those originating from MoO 3 , which is attributed to the formation of Wulfenite PbMoO 4 .…”
Section: Xrd Raman and Sem/eds Studiesmentioning
confidence: 92%
“…This observation is fully in accord with the latest high-pressure Raman work on both bulk and nanocrystalline PbMoO 4 during which a reversible second-order phase transition was only observed at much higher pressures, namely, 10.8 and 13.4 GPa, respectively. [2] These authors also reported ab initio calculated and experimental wavenumbers and pressure dependences for all 13 Raman-active modes. For the two a g modes indicated above, they obtained the following results (dn=dP values in parentheses):…”
Section: Resultsmentioning
confidence: 94%
“…[5] We observed seven clearly distinct modes in the 900-100 cm À1 region that match quite well with the literature and calculated values (see also Table 1). [2,5,12] Subsequently, we undertook variable-temperature Raman measurements at 50 C intervals from room temperature up to 600 C. All the peaks red shifted to lower wavenumbers and were broadened with increasing temperature (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation